Patients with chronic ankle instability exhibit increased sensorimotor cortex activation and correlation with poorer lateral balance control ability during single-leg stance: a FNIRS study - Liu, Na; Yang, Chen; Song, Qipeng; Yang, Fengying; Chen, Yan (Frontiers in Human Neuroscience, 2024)
Introduction: Chronic Ankle Instability (CAI) is a musculoskeletal condition that evolves from acute ankle sprains. Mounting evidence suggests that neuroplastic changes in the brain following ankle injuries play a pivotal role in the development of CAI. Balance deficits are a significant risk factor associated with CAI, yet there is a scarcity of evidence regarding the sensorimotor cortical plasticity related to balance control in affected individuals. This study aims to evaluate the differences in cortical activity and balance abilities between patients with CAI and uninjured individuals during a single-leg stance, in order to elucidate the neurophysiological alterations in balance control among patients with CAI.The study enrolled 24 patients with CAI and 24 uninjured participants.During single-leg stance, cortical activity was measured using a functional nearinfrared spectroscopy (fNIRS) system, which included assessments of the pre-motor cortex (PMC), supplementary motor area (SMA), primary motor cortex (M1), and primary somatosensory cortex (S1). Concurrently, balance parameters were tested utilizing a three-dimensional force platform.Results: Independent sample t-tests revealed that, compared with the uninjured individuals, the patients with CAI exhibited a significant increase in the changes of oxyhemoglobin concentration (ΔHbO) during single-leg stance within the left S1 at Channel 5 (t = 2.101, p = 0.041, Cohen's d = 0.607), left M1 at Channel 6 (t = 2.363, p = 0.022, Cohen's d = 0.682), right M1 at Channel 15 (t = 2.273, p = 0.029, Cohen's d = 0.656), and right PMC/SMA at Channel 11 (t = 2.467, p = 0.018, Cohen's d = 0.712). Additionally, the center of pressure root mean square (COP-RMS) in the mediolateral (ML) direction was significantly greater (t = 2.630, p = 0.012, Cohen's d = 0.759) in the patients with CAI. Furthermore, a moderate positive correlation was found between ML direction COP-RMS and ΔHbO2 in the M1 (r = 0.436; p = 0.033) and PMC/SMA (r = 0.488, p = 0.016), as well as between anteroposterior (AP) direction COP-RMS and ΔHbO in the M1 (r = 0.483, p = 0.017).Patients with CAI demonstrate increased cortical activation in the bilateral M1, ipsilateral PMC/SMA, and contralateral S1.